Symptoms accompanying congenital ranula in neonates and infants – three case reports - Krasuska-Sławińska, Ewa; Kurpiewska, Katarzyna; Olczak-Kowalczyk, Dorota; Polnik, Dariusz; Pronicki, Maciej (Pediatria Polska - Polish Journal of Paediatrics, 2020)
Congenital ranula is a rare lesion arising in the floor of the mouth, which may be asymptomatic and resolve spontaneously or can cause feeding and breathing difficulties in the child. It develops independently of systemic diseases. No diagnostic or treatment standards for congenital ranulas in neonates have been established so far. The paper describes clinical symptoms, diagnosis, and surgical management of congenital ranulas in three infants treated between 2015 and 2016 in the Children’s Memorial Health Institute in Warsaw. Due to an abnormal body weight gain and difficulty in food intake overlapping with the presence of ranula, the patients were qualified for surgical treatment.